Organic prospects - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Supporting the diversification of exports in the Caribbean/ Latin American region through the development of organic horticulture Proceedings of a conference, Port of Spain, Trinidad and Tobago, 2001. FAO, 2002. 146 pp. CTA number 1106. 10 credit point